A new Miltochrista Hübner, [1819] from Western Ghats of India (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Singh, Santosh; Singh, Navneet; Kirti, Jagbir Singh (Zootaxa, 2024)
A new species of genus Miltochrista Hübner, [1819] is described: Miltochrista coonoorensis S. Singh, N. Singh & Kirti sp. nov. from South Indian states Tamil Nadu and Karnataka. The diagnostic comparison of new species is made with five closely related congeners i.e., M. hogani Volynkin & Huang, 2022, M. ochracea (Hampson, 1891), M. obliqua (Hampson, 1891), M. hollowai Kirti & Gill, 2009 and M. uncalis (Kirti & Gill, 2009). Adult and its genital capsule are illustrated in detail.